2004
DOI: 10.1210/en.2003-1116
|View full text |Cite
|
Sign up to set email alerts
|

Apelin, a New Enteric Peptide: Localization in the Gastrointestinal Tract, Ontogeny, and Stimulation of Gastric Cell Proliferation and of Cholecystokinin Secretion

Abstract: Apelin is a recently discovered peptide that is the endogenous ligand for the APJ receptor. The aim of this study was to characterize apelin expression (mRNA levels) in the rat gastrointestinal tract and pancreas, to localize distribution of apelin peptide-containing cells in the stomach by immunohistochemistry, and to characterize the ontogeny of gastric apelin expression and peptide and the influence of apelin on gastric cell proliferation in vitro. Additionally, the effect of apelin on cholecystokinin (CCK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(151 citation statements)
references
References 24 publications
5
143
0
3
Order By: Relevance
“…Nevertheless, it should be underlined that the activation of transduction cascades by apelin-(65-77) has also been described in other cell types as well as in isolated organs (19,24,30). As we recently demonstrated that the apelin receptor is expressed by HUVEC (24), we decided to address the question of the physiological relevance of the activation and regulation of these effectors by apelin fragments in these cells.…”
Section: Regulation Of Intracellular Effectors By Apelin Fragments Anmentioning
confidence: 98%
“…Nevertheless, it should be underlined that the activation of transduction cascades by apelin-(65-77) has also been described in other cell types as well as in isolated organs (19,24,30). As we recently demonstrated that the apelin receptor is expressed by HUVEC (24), we decided to address the question of the physiological relevance of the activation and regulation of these effectors by apelin fragments in these cells.…”
Section: Regulation Of Intracellular Effectors By Apelin Fragments Anmentioning
confidence: 98%
“…Apelin was first isolated from stomach extracts, and studies on the actions of apelin in the gastrointestinal system have found functional, and possible cell survival, roles (Wang et al 2004, Susaki et al 2005, Han et al 2007). In the gastrointestinal system, apelin/APJ may be regulators of hormone (Wang et al 2004) and gastric acid (Ohno et al 2012) secretion.…”
Section: Other Functions Of the Apelinergic Systemmentioning
confidence: 99%
“…In the gastrointestinal system, apelin/APJ may be regulators of hormone (Wang et al 2004) and gastric acid (Ohno et al 2012) secretion. Apelin/APJ may also have a direct effect on vascular smooth muscle, including vasoconstriction, which may affect renal glomerular hemodynamic function in the rat kidney (Hus-Citharel et al 2008).…”
Section: Other Functions Of the Apelinergic Systemmentioning
confidence: 99%
“…Finally, adipocyte derived adipokines, such as adiponectin and leptin, also affect islet function (20,21). Although the function of apelin-36 still remains to be established, the peptide is of interest in this respect due to its localization to the stomach (8,10), adipocytes (12) and the hypothalamus (14). Its proposed action to be involved in the regulation of food intake (17) is also of interest in this context, because many bioactive peptides have the dual action to regulate food intake and islet function.…”
Section: Intravenous Glucosementioning
confidence: 99%
“…The endogenous ligand for the apj receptor is apelin, which was initially demonstrated in stomach extracts in 1998 (8). Later studies have shown that apelin mRNA is expressed in several tissues, as for example in several regions in the CNS, in the heart, lung, placenta, mammary gland and gastrointestinal tract (3,5,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%